2008
DOI: 10.21236/ada494212
|View full text |Cite
|
Sign up to set email alerts
|

Improving Magnitude Detection Thresholds Using Multi-Station Multi-Event, and Multi-Phase Methods

Abstract: Public reporting burden for this collection of information is estimated to average 1 hour per response, including the time for reviewing instructions, searching existing data sources, gathering and maintaining the data needed, and completing and reviewing this collection of information. Send comments regarding this burden estimate or any other aspect of this collection of information, including suggestions for reducing this burden to Department of Defense, Washington Headquarters Services, Directorate for Info… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2008
2008
2009
2009

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 29 publications
1
8
0
Order By: Relevance
“…Importantly, this capability is achieved with acceptably low false alarm rates as demonstrated by semiempirical synthetic runs. Similar results of this order of magnitude improvement in detection thresholds have been demonstrated by case studies using real seismic data (Gibbons and Ringdal, 2006;Schaff and Waldhauser, 2006;Gibbons et al, 2007). To estimate false alarm rates, however, synthetics must be used, or complete catalogs to lower magnitudes for denser networks on the case studies or statistical assumptions employed (Wiechecki-Vergara et al, 2001).…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…Importantly, this capability is achieved with acceptably low false alarm rates as demonstrated by semiempirical synthetic runs. Similar results of this order of magnitude improvement in detection thresholds have been demonstrated by case studies using real seismic data (Gibbons and Ringdal, 2006;Schaff and Waldhauser, 2006;Gibbons et al, 2007). To estimate false alarm rates, however, synthetics must be used, or complete catalogs to lower magnitudes for denser networks on the case studies or statistical assumptions employed (Wiechecki-Vergara et al, 2001).…”
Section: Discussionsupporting
confidence: 53%
“…Detection capability will decrease as the underlying waveform similarity decreases due to increasing interevent separation distances, mechanisms differences, and source-time function complexities. Other work has shown, however, that even semisimilar events with less-than-perfect waveform matches still provide useful detections (Schaff and Waldhauser, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is assumed that magnitude completeness of the catalog is the reason a larger improvement is not seen for closer station distances. Therefore the order of magnitude reduction in detection threshold observed for smaller studies [ Gibbons and Ringdal , 2006; Schaff and Waldhauser , 2006; Schaff , 2008] comparing correlation detectors for similar events with STA/LTA type algorithms appears to hold on a broad scale, across diverse tectonic regions, for tens of thousands of events.…”
Section: Discussionmentioning
confidence: 95%
“…Semi‐empirical synthetic runs showed this improvement is obtained with acceptable false alarm rates of about one per day [ Schaff , 2008]. A case study of 90 events in the 1999 Xiuyan earthquake sequence in China further confirmed a full magnitude unit reduction in detection threshold is possible for a different dataset and region on five regional three component stations 500 to 1500 km away [ Schaff and Waldhauser , 2006]. A key question is how well will correlation detectors work for seismicity in general on a large scale and not just specific case examples, since it requires a priori information on the shape of the master waveform template?…”
Section: Introductionmentioning
confidence: 99%